Half a century of IgA nephropathy: achievements, frustrations and challenges - I.I. Lapchynska (Український Журнал Нефрології та Діалізу, 2018)
IgA nephropathy is the most common glomerulonephritis worldwide. This disease has a tremendous economic impact because renal replacement therapy is expensive and hard-to-reach. It also represents a social problem because children and young adults in their second and third decades of life are affected by the IgA nephropathy, and it is the most active period of human life with highest work productivity. Many retrospective studies have shown that 40% of biopsy-proven IgA nephropathy patients develop end-stage kidney disease in 20 years after their biopsy disease.